2021
DOI: 10.21009/jobbe.005.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Entrepreneurship Education in Universities

Abstract: The purpose of this study is to systematically review the recent publications in Entrepreneurship Education in Universities (EEU) by considering the key characteristics and contributions of the articles. The study employed the Systematic Assessment Quantitative Technique (SQAT) developed by Australian researchers, Catherine Pickering and Jason Antony Byrne to identify and analyze 60 peer-review EEU articles. The result showed that Europe, followed by Africa had the highest geographical spread of EEU articles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…It is, therefore, the view of the researchers that if business education students can be skillful in the identified entrepreneurial skills they will be self-reliant and also, in the long run, become employers of labor. The findings corroborate the views of Igbo (2009) and Ezeh (2012) which revealed that the acquisition of entrepreneurial skills prepares and develops students' potential for the attainment of self-reliance, thereby contributing to sustainable development.…”
Section: Discussionsupporting
confidence: 88%
“…It is, therefore, the view of the researchers that if business education students can be skillful in the identified entrepreneurial skills they will be self-reliant and also, in the long run, become employers of labor. The findings corroborate the views of Igbo (2009) and Ezeh (2012) which revealed that the acquisition of entrepreneurial skills prepares and develops students' potential for the attainment of self-reliance, thereby contributing to sustainable development.…”
Section: Discussionsupporting
confidence: 88%